2021
DOI: 10.1017/s0007114521003780
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probiotics/synbiotics supplementation on renal and liver biomarkers in patients with type 2 diabetes: a systematic review and meta-analysis of randomised controlled trials

Abstract: Despite the apparent beneficial effects of probiotics/synbiotics on glucose hemostasis, lipid profile, and inflammatory responses, it is not clear whether these beneficial effects also impact renal and hepatic function in diabetes. Therefore, we sought to assess the effect of probiotics/synbiotics supplementation on renal and liver biomarkers in adults with type 2 diabetes (T2DM) using a systematic review and meta-analysis of randomized controlled trials (RCTs). PubMed, Scopus, Web of Science, and Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
1
7
0
1
Order By: Relevance
“…Our study findings showed a significant decrease in blood creatinine. This finding was consistent with the systematic review and meta-analysis findings on the use of probiotics and synbiotics that indicated a decrease in blood creatinine levels ( 43 ). We observed a significant reduction in CRP, which confirmed the findings of a clinical trial study that showed a significant reduction in inflammatory outcomes following supplementation with vitamins A, B, C, D, and E ( 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our study findings showed a significant decrease in blood creatinine. This finding was consistent with the systematic review and meta-analysis findings on the use of probiotics and synbiotics that indicated a decrease in blood creatinine levels ( 43 ). We observed a significant reduction in CRP, which confirmed the findings of a clinical trial study that showed a significant reduction in inflammatory outcomes following supplementation with vitamins A, B, C, D, and E ( 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…While cinnamon and L. acidophilus may work additively or synergistically as potential therapeutic compliments in patients with T2DM, their interactions may be altered based on the patients' comorbidities and atypical hepatic functions. A metaanalysis discussing the effects of probiotics and synbiotics on liver and renal biomarkers in T2DM patients obtained results running mostly in parallel to this paper, with some exceptions (85): even though Abdollahi et al concluded with insignificant changes in liver biomarkers overall, their results were based on a smaller sample size with limited focus on the isolated effects of the nutraceuticals studied (85).…”
Section: Current and Future Directives For Synbioticsmentioning
confidence: 60%
“…Although ours is the first comprehensive analysis of the effect that pro/pre/synbiotics have on various renal parameters in diabetics, previous systematic reviews and meta-analyses have independently and exclusively investigated the effect of pro/pre/synbiotics on renal markers in only T2D, DN/DKD, or other diseases. In a study by Abdollahi et al [ 5 ], pooled results from six pro/synbiotic administering RCTs revealed significant changes of −0.10 mg/dL (95% CI: −0.20; −0.00) in serum Cr among T2D participants; however, the study found no significant effects on eGFR, Alb/Cr ratio, or BUN. Similar results were found by Tarrahi et al [ 68 ] from their analysis of seven trials administering probiotics in DN patients, revealing significant changes of −0.18 mg/dL (95% CI: −0.26; −0.09) in serum Cr, but no change in BUN or GFR.…”
Section: Discussionmentioning
confidence: 98%
“…T2D often leads to debilitating macrovascular complications, such as cardiovascular disease (CVD) [ 3 ], as well as microvascular complications such as retinopathy, neuropathy, and nephropathy [ 4 ]. Afflicting 20–40% of diabetic patients, diabetic nephropathy (DN), or diabetic kidney disease (DKD), is a complex and multifactorial complication of diabetes involving hyperglycemia, atherosclerosis, obesity, dyslipidemia, hypertension, and increased glomerular pressure [ 5 , 6 , 7 ]. DKD is also one of the leading causes of end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%